2006
DOI: 10.1175/jpo2930.1
|View full text |Cite
|
Sign up to set email alerts
|

Circumpolar Deep Water Circulation and Variability in a Coupled Climate Model

Abstract: The natural variability of Circumpolar Deep Water (CDW) is analyzed using a long-term integration of a coupled climate model. The variability is decomposed using a standard EOF analysis into three separate modes accounting for 68% and 82% of the total variance in the upper and lower CDW layers, respectively. The first mode exhibits an interbasin-scale variability on multicentennial time scales, originating in the North Atlantic and flowing southward into the Southern Ocean via North Atlantic Deep Water (NADW).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 76 publications
(107 reference statements)
4
20
0
1
Order By: Relevance
“…This warm, salty signal connects into the upper CDW. This is consistent with a modeling study by Santoso et al (2006), which showed that a significant portion of upper CDW T-S variability originates within the Brazil-Malvinas confluence via meridional advection. The anomalous signal then propagates into the Southern Ocean CDW via the ACC.…”
Section: G Internal Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…This warm, salty signal connects into the upper CDW. This is consistent with a modeling study by Santoso et al (2006), which showed that a significant portion of upper CDW T-S variability originates within the Brazil-Malvinas confluence via meridional advection. The anomalous signal then propagates into the Southern Ocean CDW via the ACC.…”
Section: G Internal Propertiessupporting
confidence: 92%
“…The projected salination and warming signal seen in most models south of 408S reflect changes in CDW. While changes in CDW could occur through property changes in NADW or via changes in the rate of diapycnal mixing with neighboring AAIW/AABW (Santoso et al 2006), such mechanisms would not result in changes consistent with those projected. Instead, the dominant mechanism appears to be an increased southward and upward transport of freshwater and heat, within the CDW, associated with the spinup of the Deacon circulation.…”
Section: G Internal Propertiesmentioning
confidence: 99%
“…The variations of the vertically integrated heat content amount to about 640 3 10 21 J in the Atlantic Ocean basin-Indian Ocean Basin, defined here as the region 408-908S and 708W-808E. The heat is provided by the lower branch of the AMOC, a mechanism previously described from uncoupled ocean model simulations (Mikolajewicz and Maier-Reimer 1990;Yin and Sarachik 1995;Pierce et al 1995) and coupled climate model simulations (Santoso et al 2006). During phases of deep convection, large amounts of heat are released to the atmosphere in the KCM, similar to what was observed during the Weddell Polynya (Moore et al 2002).…”
Section: Climate Model Resultsmentioning
confidence: 91%
“…Observational studies estimate that the Southern Ocean transports distinct varieties of AABW equatorward into the subtropical Atlantic, Pacific, and Indian basins at a net rate of roughly 20 Sverdrups (Sv; 1 Sv [ 10 6 m 3 s 21 ), primarily via a network of deep western boundary currents (DWBCs) (Lumpkin and Speer 2007;Purkey and Johnson 2012). The inflow of LCDW is also thought to occur primarily via DWBCs and is composed of a mixture of North Atlantic Deep Water (NADW) from the Atlantic basin and recirculated deep waters from the Indian and Pacific Oceans (Jacobs 2004;Santoso et al 2006). Together, these meridional flows into and out of the Southern Ocean play an important role in the storage and transport of carbon, heat, and other geochemical tracers (e.g., Levitus et al 2005) and consequently may play a significant role in global climate change (e.g., Meehl et al 2006).…”
Section: Introductionmentioning
confidence: 99%